Building Confidence: Grade VII Students’ Participation in School Competitions - Ibrahim Muhammad Yusuf Zakaria (PSDKU Guidance and Counseling, Universitas Negeri Surabaya, 2025)
This study aims to describe the self-confidence of seventh-grade students in participating in school competitions and the factors that influence it. The research employed a descriptive qualitative approach with interviews and observations as data collection techniques. The research subjects consisted of one seventh-grade student participating in a speech competition and one supervising teacher selected through purposive sampling. The collected data were analyzed using Miles & Huberman’s interactive analysis model, which includes data reduction, data display, and conclusion drawing. The results showed that teacher support, peer encouragement, family motivation, and intensive practice were the main factors that help enhance student self-confidence. Meanwhile, the inhibiting factors included fear of making mistakes, nervousness when performing in public, and feelings of inferiority compared to other participants. After participating in the competition, the student demonstrated increased confidence in learning activities and appeared more comfortable speaking in front of the class. Future studies are recommended to involve a larger number of participants, explore different types of competitions, and consider additional psychological aspects such as self-efficacy and performance anxiety to strengthen the generalizability and depth of the findings.